Nyai leadership: The role of women in maintaining the tradition of santri literacy in islamic boarding schools - Herlina Herlina; Munawara Munawara; Irmak Sude Gurel (An-Nisa’ Journal of Gender Studies, 2025)
Islamic boarding schools (pesantren) have a strong literacy tradition, yet female leaders’ roles in sustaining it are often overlooked. Recognizing their visionary, participatory leadership is essential to understanding how they foster student motivation, literacy practices, and integration of cultural, institutional, and pedagogical dimensions. This study aims to analyze the leadership role of Nyai (wife of the Kiai) in sustaining and developing the literacy culture of santri in pesantren through leadership transformation, the strengthening of literacy institutions, and the establishment of a santri literacy ecosystem. A qualitative phenomenological approach was employed, with data collected through in-depth interviews, participant observation, and document analysis. The data were analyzed thematically using triangulation of sources, methods, and time to ensure credibility, capture participants’ subjective experiences, and connect the findings with theories of women’s leadership. The study finds three key points. First, the Nyai's leadership transformed into competence-based institutional authority via mandatory reading programs and restructuring. Second, literacy reinforcement combined regulations with non-formal policies, expanding academic spaces and santri participation. Third, literacy success relied on synergy among visionary leadership, santri motivation, spiritual climate, institutional support, and trust in santri to manage literacy. The study concludes that Nyai's leadership transforms from domestic companion to competence-based institutional authority, synergizing visionary leadership, student motivation, and trust to make literacy an institutionalized and regenerated intellectual heritage. This study contributes to enriching transformational leadership and institutional work models, offering a practical literacy empowerment model for Islamic schools.